Os métodos consensuais de solução de conflitos para o alcance de uma cultura de paz - Prates Junior, João Carlos Magalhães (2018)
The proposal of this master's thesis is based on the demystification of the judicial process - which, in practice, dominates the eyes of the rulers when the subject is incentive and diffusion of methods of promotion of Justice - and the deconstruction of some dogmas that revolve around him, to demonstrate that it is absolutely necessary to open the mind of society as a whole to finally address our conflicts in a peaceful, civic, friendly and humane manner. For this, it is essential to regain autonomy of individuals to solve their own conflicts, empowering them and giving them an active voice in what concerns their own life. Law, when the subject is conflict, has always appropriated this phenomenon, calling itself the only and best science capable of solving it. Because of the complexity of the conflict phenomenon, it is necessary to have a composition of knowledge, concretized in practice by the multidisciplinary and interdisciplinary action of the different areas of science, in order to better understand the conflicts and the people who compose them, only thus, it helps them to solve them. It is the case, then, to borrow knowledge also from psychology, philosophy, sociology, medicine, social assistance, etc. In a Brazil where the culture of the sentence is largely massified, and in a world of mass domination, to propose pacification is an arduous but necessary task, to propose the recovery of the autonomy of society, when it is taken up by the rulers as a danger to its own status of "Power," is military on a ground almost invincible. However, the growth of consensual conflict resolution methods, such as mediation, conciliation and negotiation, is visible and this dissertation intends to exalt them even more